UNCONSCIOUS MOTIFS IN HARUKI MURAKAMI’S NORWEGIAN WOOD (International Journal of Food and Nutritional Sciences, 2022)
This research on Murakami’s Norwegian Wood attempts to explore how recurring images like music, water, silence, and death can articulate a complex narrative of the unconscious. Psychoanalytic theories provide the grounding where Freud suggests repression and dream work as central mechanisms of psychic life, and Jung suggests individuation within the encounter between ego and shadow. Each motif in Murakami’s novels performs a precise symbolic function within the theoretical frame. Music functions as a sound trigger for the memories that are deep inside. Water and rainfall mirror the turbulence of the suppressed feelings, and the silence reveals loneliness and the ache of absence which words cannot express. Death does not give an ending, they lingers in the air and shapes the living. Naoko, the central character deeply hurts Toru’s sense of self. Through these symbols, Murakami reveals the struggles that the characters face. This exploration shows how he threads the unconscious elements into the novel which creates an inward and emotional journey transforming personal grief into a deeply felt experience.